(3QSGdI aj Gdadcs
(3ChdgG (B:s
(3GdSWM YfO fbUGf GdYQV efg dCfg dh de jfbU dcGf SWMkG dGNWkG s
(3BNQgG (B:s
(3aGNJUQ HHYV GdeSGFd djUjQ bGQFg UGMH HUjQI ai gPG Gdaf GdcJH GdeWhdI HYO aQGZg dCecfg hGddg CYde Je GdbSe GdJGSY hgh bSe ef LGeY Gdafhf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3HgG fXGe GdJYbjHIs
(3JTJed Ydi QShe gfOSjIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdeLGejYs